Inclusiveness of Catering Services for The Customer with Special Requirements - Matylda SIWEK; Anna KOLASINSKA; Mariusz CEMBRUCH-NOWAKOWSKI (Communications of International Proceedings, 2022)
The phenomenon called inclusiveness has been widely discussed in the context of tourism. It refers to all tourist groups which might be marginalised due to their age, physical or mental condition, and different types of disabilities. The catering industry that serves both tourists and local communities, has also recognised the need of providing access to all customers groups. In the up to now literature on inclusive tourism, issues of catering services have rarely been addressed and have usually focused on a selected group of consumers. The aim of the study was to determine the scale of inclusivity for the catering industry on the example of Krakow – one of the oldest and most touristic cities in Poland. The following research questions have been raised: What types of activities in the area of inclusivity are undertaken by catering premises in Krakow and which of these activities are dominant? The survey method has been used to carry out the research by means of a questionnaire in paper form. 169 restaurants took part in the research. They are located in the area of the most touristic districts, which has been divided into three parts. To illustrate the degree of diversification of activities regarding the inclusiveness in the gastronomy industry in the researched area, the E.C. Amemiya (η) Economic Base Diversification Index has been adopted and used. From the obtained results it can be concluded that the phenomenon of inclusiveness in the surveyed restaurants in Krakow does occur and that the degree of differentiation of inclusive activities of the catering premises in Krakow is high. The research has shown that the most frequently undertaken inclusive activities are those aimed at families with children.
Keywords: Inclusiveness; restaurants; special requirements; people with disabilities; families with children; seniors